Reducing severance costs or subsidizing permanent job creation: Which policy is more effective to reduce duality? - Victoria Osuna (Kiel Institute for the World Economy (IfW), 2015)
This paper uses the job creation and destruction model of the search and matching type proposed by García-Pérez and Osuna (2014) to study the effectiveness of subsidizing permanent job creation as a strategy to reduce labour market segmentation between permanent and temporary contracts. The 2006 and 2012 Spanish labour market reforms are used as a benchmark to compare the effects of subsidizing permanent job creation with that of reducing the severance cost gap between permanent and temporary contracts. The change in the degree of duality is measured in terms of the changes in job destruction rates and the tenure distribution. The steady-state results show that, from a fiscal point of view, reducing the severance cost gap between these two type of contracts may be more effective than subsidizing permanent job creation, provided dismissals for objective reasons are effectively made easier to justify and firms make use of that option instead of agreeing to an indemnity closer to the amount paid for unfair dismissals. The model also points to the relevance of designing appropriate penalties for those firms that do not comply with the obligations that subsidies involve. Finally, the sensitivity analysis reveals the importance of the magnitude of training costs and the relative differences in productivity between temporary and permanent workers for the effectiveness of policies involving subsidies for permanent job creation.
Keywords: J23; J32; J63; J64; J65; J68; 330; Subsidies; Severance Costs gap; Permanent and Temporary Contracts; Duality; Unemployment; Tenure Distribution; Job Destruction